Analysis of PSAP 17 Investment Property Implementation in the Central Government Financial Report (LKPP) - Akbar, Ilham; Wardhani, Ratna (E-Jurnal Akuntansi; Vol 34 No 12 (2024), 2024)
This research aims to evaluate the process and constraints of the impact of the implementation of PSAP 17 Investment Property in the Central Government Financial Report (LKPP) and the relevance of the use of fair value in accordance with IPSAS 46 Measurement in the presentation of Investment Property for Stakeholders of LKPP. The method used is a qualitative method through a case study approach on the implementation of PSAP 17 and a simulation method in the restatement of investment property values using fair value measurements. The results of the study indicate that the presentation of investment property in LKPP is in accordance with PSAP 17 but is more relevant for stakeholders of LKPP if presented using fair value measurement. This study recommends that in order to accelerate the presentation of investment properties in LKPP, it is necessary to improve the competence of the government financial report preparation team and improve the integrated government financial application system as well as propose a revision to government accounting standards that allow for periodic fair value measurements .